Usia 6-9 : Status Gizi Terhadap Kebugaran Jasmani Anak - Sapika, Sapika; Djalil, Rasyidah; ulpi, wahyuni; Hakim, Nurwahidin (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
The nutritional status of children on physical fitness is necessary to support the children’s activities, including exercising. This study was conducted to discover whether there is a relationship between children's nutritional status and physical fitness. This is a quantitative research, where the research was conducted in the sub-district of Bua, Luwu Regency, this research used purposive and snowball sampling with several criteria for children aged 6-9 years. The number of samples involved in this research are 10 people, 5 boys and 5 girls. The instruments used to measure the nutritional status of children with physical fitness are body max index (BMI) and the Indonesian physical fitness test (TKJI). The results of the data were analyzed using the SPSS application. The average value of physical fitness is 80% in the (moderate) category while the average value of the nutritional status of children is 90% in the normal category. the results of descriptive analysis of the nutritional variable, the lowest value is 13.3 and the highest value is 19.2 with an average value of 18.8 and the standard deviation of the data distribution level of 1.90 while the TKJI variable has the lowest value of 13 and the highest value of 19 with an average value of 1.9. From the research data and analysis carried out, it was concluded that the significant value was 0.002 <0.05, Thus it means that there is a relationship between nutritional status and physical fitness with the meaning of H¹ being accepted.